Perceptual-cognitive expertise in combat sport: from scientific research to training - Martinez de Quel, O.; Bennett, S. J. (Revista de Artes Marciales Asiaticas, 2016)
Performance in combat sports has been widely studied from the point of view of physiology, anthropometrics or biomechanics. Thus, conditional training is usually based on physiological research and techniques are evaluated from a biomechanical perspective. However, combat sport experts also differ from novices in their psychological characteristics. In fact, many trainers suggest the difference between a good athlete and a champion is the ability to make the right technique at the right moment, and that this requires expert perception, cognition, decision making, and tactical awareness. Given the importance of psychological characteristics, it is somewhat surprising that they are usually trained using methods based on the experience of the coach more rather than scientific research. Our aim, therefore, was to review relevant scientific literature on combat sports expertise in a selection of perceptual -cognitive variables and then to provide some guidelines for training.